An exceptional Pleistocene specimen of Panochthus Burmeister (Xenarthra, Glyptodontoidea) from Bolivia: Its contribution to the understanding of the Early-Middle Pleistocene Panochthini - Zurita, Alfredo Eduardo (2011)
Knowledge of the Early-Middle Pleistocene (Ensenadan Age/Stage ; ca. 1.8-0.4 Ma) South American Glyptodontidae (Cingulata) is still poor compared with the Late Pleistocene-Early Holocene taxa (Lujanian Age/Stage). This is especially true for the Glyptodontidae Panochthini, in which it is possible to recognize two Ensenadan species from the Pampean region of Argentina, Panochthus intermedius and P. subintermedius, known only by their type material. Prior to this contribution, the knowledge of P. intermedius, a taxon with biostratigraphic importance for being considered as a guide taxon of the Ensenadan Age/Stage of South America, was limited to a dorsal carapace. The finding of an exceptional almost complete specimen from the Early-Middle Pleistocene of Bolivia has allowed us to greatly improve the morphological characterization of this species, and discuss some taxonomic aspects related to the other Ensenadan Panochthini. This specimen represents the most completely known Panochthini and one of the most complete Glyptodontidae from the Early-Middle Pleistocene of South America.